PENGARUH PERBANDINGAN TERIGU DAN TEPUNG KACANG TUNGGAK TERHADAP KARAKTERISTIK CRACKERS - Lestari, Putri Anggun; Yusasrini, N. L. Ari; Wiadnyani, A.A. Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i04.p12, 2019)
This study aims to determine the effect of comparative of wheat and cowpea flour to characteristics of crackers andto knowing the composition to produce crackers with the best characteristics. The experimental design used was Completely Randomized Design with treatment factor that is the comparative treatment of cowpea flour with wheat which consist of 5 levels : 100%:0%, 95%:5%, 90%:10%, 85%:15%, and 80%:205. The treatment was repeated 3 times to obtain 15 units of experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continoued with Duncan test. Result of this study showed that comparation of wheat flour and cowpea flour very affected for protein content and coarse fiber content, affected water content, ash content, color, texture, and overall acepatance. Comparation of 80% wheat flour and 20% cowpea flour is the best characteristics of crackers with criteria 2.24% water contet, 2.62% ash content, 23.93% fat content, 10.70% protein content, 61.28% carbohydrate content, 6.61% crude fiber content, 0.44 power of broke, the color was liked, the aroma was neutral, the taste was liked and a little typical of cowpea, texture was crunchy and liked, and overall aceptance was liked. Keywords: Crackers, cowpea flour, wheat flour.